QUALITY INSPECTION RAW FOOD AND FRUITS USING IOT AND IMAGE PROCESSING - D., Pooja; J., Mohana (International Journal of Psychosocial Rehabilitation, 2020)
Recent trends in technology have made it possible for the stakeholders in the agricultural sector to develop their products and provide advanced services. A positive transition from proprietary to IoT-based, open systems to make collaboration between stakeholders more efficient is underway. The technical support for application developers to start specialized services that connect seamlessly. This approach includes creating an advanced and tailor-made environment for end users. Our proposal is to incorporate an architecture that initiates this approach on the basis of the'' common enabling'' domain-independent framework built under the FI-WARE project. This application is used to test other creative ideas, such as the idea of the market place of the services and the adjustment of network failures, for the agriculture industry. The evaluation results show that the program is appropriate and that farmers need access to sophisticated facilities at an accessible price. The evaluation results The applications, hardware and IoT technologies are included.